PS01.133: ISCHEMIC CONDITIONING OF THE STOMACH PRIOR TO ESOPHAGECTOMY: TIMING AND TECHNIQUE MATTER. (14th September 2018) - Carrott, Philip; Shih, Terry; Reddy, Rishi; Erickson, Crystal; Lagisetty, Kiran; Lin, Jules
Abstract: Description: This video highlights one method of gastric ischemic conditioning prior to esophagectomy. Multiple reports of ischemic conditioning have not shown benefit, but these studies generally had a short time of ischemia (7–14 days), and did not have a consistent method of conditioning that includes both short gastric and left gastric vessels. Animal data shows that 30 days is likely the minimum timing needed for development of collateral blood flow through the body of the stomach. We have treated 13 patients with between 35 and 180 days of ischemic conditioning prior to esophagectomy, and none of these patients developed a leak, with only one requiring dilation of a benign anastomotic stricture. In these patients, 5 patients underwent a concominant feeding jejunostomy. In our experience, ligation of the arterial and venous blood supply is important, as is ligation of both short gastric and left gastric vessels. If the left gastric vessels cannot be seen, lesser curvature perforating vessels high on the proximal stomach may be ligated as well. We prefer to use the laparoscopic clips to ligate these vessels, while some groups use energy devices to divide the short gastric vessels and clips to occlude the left gastric vessels. This keeps the subsequent adhesive disease to a minimum, which is likely the major barrier to longer conditioning time. Indeed, the ideal timing of the ischemic conditioning procedure is prior to starting chemo-radio-therapy, giving 100 days or more of conditioning time. The video outlines a laparoscopic procedure that we feel is optimum for ischemic conditioning of the stomach. We believe this method has cracked the code of a very morbid procedure and made it into a slightly morbid procedure, which can still have complications, but the anastomotic complications are much less severe with improved perfusion to the gastric conduit. Leaks are less frequent and less severe, and symptomatic strictures are fewer in number. Future work in this area should focus on ischemic conditioning timing, as well as cancer-specific outcomes related to the conditioning procedure. Disclosure: All authors have declared no conflicts of interest.